Workplace Innovations in Large, Unionized Canadian Organizations - Balkin, David B.; Tremblay, Michel; Westerman, James (Journal of Business and Psychology, 2001)
The study reports workplace innovations in 112 large, unionized Canadian organizations from data collected in 1994 by the Bureau of Labour Information. The frequency of specific workplace innovations and the relationship to organization and bargaining unit characteristics are reported.